(untitled) (Research, Society and Development, 2020)
This case study aims to present an experience of acting as Interpreter Translator of Brazilian Sign Language (Libras) and Portuguese Language (TILSP) during the Special and Inclusive Education discipline in a class of Letters - Degree in Libras / Portuguese as a Second Language, at the Federal University of Rio Grande do Norte (UFRN), attended by 15 deaf students. It was noticed the lack of prior knowledge of these students about the themes of the Inclusive Education area that do not include deaf education, as it is not part of the reality experienced by them and an initial lack of interest towards the discipline itself. With the task of translating and interpreting the didactic-pedagogical activities developed in educational institutions, in order to enable access to knowledge of curricular contents, the TILSP professional has the implication of acting not only as a linguistic mediator between deaf people and Libras non-users hearing people, but also be an active participant in the teaching-learning process of the deaf student, being a collaborator of the teacher responsible for the discipline. Given what the deaf students demonstrated at the beginning and end of the semester regarding the learning of curriculum related to the discipline of Inclusive Special Education and considering the role of TILSP as a linguistic mediator and educational participant, it was found that the students could effectively have the appropriate accessibility to the subject. proposed knowledge in this reported context.